(untitled) (Cadernos de Sociomuseologia, 2009)
The Construction of the museological object "Exhibiting is or should be to work against ignorance, especially against the most refractory of all ignorance: the pre-conceived idea of stereo typed culture. To exhibit is to take a calculated risk of disorientation - in the etymological sense: (to lose your bearings), disturbs the harmony, the evident , and the consensus, that constitutes the common place (the banal). Needless to say however it is obvious that an exhibition that deliberately tries to scandalise will create an inverted perversion which results in an obscurantist pseudo-luxury - culture ... between demagogy and provocation, one has to find visual communication’s subtle itinerary. Even though an intermediary route is not so stimulating: as Gaston Bachelard said "All the roads lead to Rome, except the roads of compromise." It is becoming ever more evident that museums have undergone changes that are noticeable in numerous areas. As well as the traditional functions of collecting, conserving and exhibiting objects. museums have tried to become a means of communication, open and aware of the worries of modern society. In order to do this , it has started to utilise modern technology now available and lead by the hand of "marketing" and modern business management.